Стадії політичного процесу - теоретичні аспекти - Мацкевич, Р. М.; Мацкевич, Р. М.; Mackevich, R. (My University, 2011)
Questions of political process structure which consists of row of stages consistently accomplished and cyclic repetitive are examined in the article. Analysis of political process allows to distinguish in its structure, at ﬁ rst, partial political processes or groups of relatively independent political actions, which forms in aggregate motion of political life on the whole, secondly, stages in change of state of political reality.
Мацкевич Р. М. Стадії політичного процесу - теоретичні аспекти / Р. М. Мацкевич // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. – Одеса : Фенікс, 2011. – Вип. 42. – С. 57 - 61.
Keywords: стідії політичного процесу; політичний процес; політика; політична система; политическая система; политика; политический процесс; стадии политического процесса; political system; politics; political process; stage of the political process